2005
DOI: 10.1007/s00383-005-1560-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of serial computed tomographic scanning in pediatric severe traumatic brain injury

Abstract: The purpose of this study is to determine whether serial computed tomography (CT) scans of the head lead to operative intervention in pediatric patients with severe traumatic brain injury (TBI). Serial CT scans are those done in addition to the initial CT scan and one follow up CT scan in the first 24-48 h. This study is a retrospective review from January 1990 to December 2003. The hospital course was reviewed for 942 pediatric patients with traumatic brain injuries. Of these, 40 patients were identified who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
2
33
2
Order By: Relevance
“…However, case reports of delayed traumatic epidural and subdural hematoma after an initial lucid period (9,10) have led some to consider routinely repeating CT even in the absence of any clinical signs of deterioration (3,4,11). In theory, routinely repeated head CTs could identify new or worsening TBI before permanent neurologic damage occurs, thereby enabling early intervention and improvement in outcomes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, case reports of delayed traumatic epidural and subdural hematoma after an initial lucid period (9,10) have led some to consider routinely repeating CT even in the absence of any clinical signs of deterioration (3,4,11). In theory, routinely repeated head CTs could identify new or worsening TBI before permanent neurologic damage occurs, thereby enabling early intervention and improvement in outcomes.…”
mentioning
confidence: 94%
“…There is little information about the diagnostic and therapeutic impact of repeated head CT for pediatric blunt head injury, and opinion is divided on the value of routinely repeating imaging at a prescheduled interval postinjury (4,6,11).…”
mentioning
confidence: 99%
“…However, increased awareness of the risks of HCT and the lack of evidence supporting its use suggest that routine follow-up HCT may not be justified in this patient population. In fact, numerous studies do not support routine repeat HCT without changes in clinical exam or neurological deterioration [5,6,7,8,9,10,11,12,13,14,15]. However, most of these studies were conducted in adults; it is unclear if these findings can be extrapolated to children.…”
Section: Discussionmentioning
confidence: 89%
“…In a study by Isik et al (25), 89.2% of patients were shown total recovery, 7% was discharged by sequelae and the mortality rate was reported as 3.8%. Figg et al reported that the emergent operations were applied to the patients with serious TBI in repeated CT screening and only with increased intracranial pressure (21%) and deterioration in neurological findings (3%) (26). They also reported that emergent operation application is not necessary for the patients who had CT screening without any routine findings.…”
Section: Discussionmentioning
confidence: 99%